Isolated multiple cutaneous verruciform xanthomas (Indian Journal of Case Reports, 2019)
Verruciform xanthoma (VX) is a rare benign skin condition, primarily of the oral mucosa that can also affect the skin and genital mucosa. The etiology is not yet completely understood; though its association with conditions of chronic inflammation or trauma, chronic lymphedema, chronic graft versus host disease and CHILD syndrome are mentioned in the literature. Here, we report the case of multiple verruciform xanthomas on the bilateral forearms and upper back of a 25-year-old man in the absence of chronic skin disease or systemic disease and surprisingly, he didn’t have mucosal VX too. Histopathology of the lesion showed nodular dense infiltrate of foamy macrophages in the papillary dermis which stained positive for CD68.